Price convergence in the Central American regional electricity market - Cont, Walter Alberto (2021)
After 7 years since the formalization of the regional electricity market (MER, according to the Spanish acronym) in Central America, operating in a parallel fashion with domestic markets, we study the evolution of spot prices to understand whether the MER allowed for price convergence in the transactions that took place among countries. We use a test proposed by Phillips and Sul (Econometrica, 2007) to run the convergence test and find that long term forces are in effect, interrupted temporarily in mid-2016 after the introduction of a hydroelectric plant (Reventazon) in Costa Rica. This convergence result is accompanied by indirect evidence of a reduction in the level of spot prices during the period (after having considered the cost of fuels or natural gas).